Overview of Human Rights for Indonesian Migrant Worker Children to Receive An Education at The Hulu Langat Malaysia Guidance Studio - Taufiq Hidayat; Ambiro Puji Asmaroini; Sunarto .Sunarto; Sulton Sulton; Zamawi Chaniago (Qalamuna, 2023)
Human rights are fundamentally crucial to every individual, especially the right to education, which has been stipulated in the Indonesian constitution, not only Indonesia but international agreements have also stipulated that human rights apply to every individual by the implementation of this research. This aims to obtain information related to what causes the children of migrant laborers from Indonesia to have undocumented status and what problems are faced in obtaining Children of undocumented Indonesian migrant workers access to schooling, then what efforts and solutions can be made in obtaining education in Malaysia. Children of Indonesian migrant laborers who are undocumented. The researchers use qualitative methods and a systematic approach. Using methods for gathering data, such as interviews, observations, and documentation. Several reasons result in Malaysian migrant workers from Indonesia whose children lack proper documentation, including because they entered Malaysia illegally. Without having a valid work document, the validity period expires (overstaying), and getting married in Malaysia to another foreign citizen. There were problems with the rights of Malaysian migrant workers from Indonesia to send their kids to school, so the Hulu Langat guidance studio was established to overcome the problems, helping the kids of illegal Indonesian migrant laborers to help them get an education in Malaysia. With these causes resulting in their children having document status and with the establishment of the Hulu Langat guidance studio as a means of resolving the issues that Indonesian migrant workers' kids face, this has made a positive contribution to fulfilling the educational rights of the workers' children. Migrants from Indonesia in Malaysia, particularly young children, without proper documentation.